Rezeption kritischer Perspektiven auf postkoloniale Theorie - Freuding, Janosch (2023)
Postcolonial approaches have only recently been more widely received in German-language religious education. In this reception, it is important to also take into account points of criticism of postcolonial theory. This article offers an overview of relevant critical perspectives – and, against this background, sheds light on existing potentials for religious education processes.
Postkoloniale Ansätze werden in der deutschsprachigen Religionspädagogik erst seit Kurzem verstärkt rezipiert. Bei dieser Rezeption ist es wichtig, auch Kritikpunkte an der postkolonialen Theorie mitzuberücksichtigen. Vorliegender Beitrag bietet eine Übersicht über relevante kritische Perspektiven – und beleuchtet vor diesem Hintergrund weiterhin bestehende Potenziale für religiöse Bildungsprozesse.
Keywords: intersektional; Religionspädagogik; Antisemitismus; postkolonial